HIV-associated gut dysbiosis drives oncogenesis through metabolic-immune crosstalk: mechanisms and therapeutic implications - Meng, Qingquan; Xu, Liran; Xu, Furong; Shen, Xiaohan; Yue, Jingyu (Frontiers in Oncology, 2025)
HIV-induced gut microbiota dysbiosis perpetuates mucosal barrier disruption and systemic inflammation despite antiretroviral therapy (ART), creating a tumor-permissive microenvironment. This review synthesizes evidence linking HIV-associated microbial alterations to oncogenesis through three convergent metabolic axes: (1) butyrate deficiency impairing epithelial energy metabolism and anti-tumor immunity; (2) tryptophan metabolism dysregulation compromising gut barrier integrity via Akkermansia muciniphila depletion and Enterococcus-mediated phenylethylamine overproduction; and (3) vitamin B biosynthesis defects disrupting DNA repair and Th1/Th2 balance. Comparative profiling across HIV-associated malignancies—non-Hodgkin lymphoma, cervical cancer, hepatocellular carcinoma, and lung cancer—reveals conserved dysbiotic signatures: depletion of anti-inflammatory taxa (Bacteroidetes, Bifidobacterium) and expansion of pro-inflammatory genera (Proteobacteria, Shigella). These alterations activate NF-κB/STAT3 signaling, fostering IL-6/TNF-α-driven chronic inflammation. Emerging interventions, including Bifidobacterium-derived metabolites and butyrate supplementation, demonstrate potential to enhance immunotherapy efficacy and reverse chemoresistance. However, causal microbiota-tumor relationships remain unproven, and key AIDS-defining cancers (Kaposi sarcoma, anal carcinoma) lack microbial association studies. Prioritizing longitudinal multi-omics analyses, organoid models, and LMIC-focused clinical trials may advance microbiota-directed strategies for HIV-associated cancer prevention and treatment.